Temperature Dependence of Ultrasonic Waves Properties Propagated in Some Types of Carbon Steels - Luong, Thi Minh Thuy (H. : ĐHQGHN, 2017)
In this research, properties of ultrasonic waves transmitted in some carbon steels were investigated. Base on ultrasonic measurements for the steel samples of X40H, S45, SCM420, and SCR420, the values of ultrasonic wave velocities including longitudinal and transverse velocities were determined. These measurements also used to obtain ultrasonic attenuations of these steel samples. Based on ultrasonic velocities, the mechanical properties of these steel samples were calculated including Poisson’s Ratio υ, Young’s modulus E, and Shear modulus G. The experimental results show that these mechanical parameters were linearly depended on the carbon steel samples’ temperature.